Non-Cardiogenic Pulmonary Oedema Following the use of Gadolinium-Based Contrast Medium: A Case Report - Nguyen, Chilan (J Crit Care Med (Targu Mures), 2020)
Non-cardiogenic pulmonary oedema can be life threatening and requires prompt treatment. While gadolinium-based contrast is generally considered safe with a low risk of severe side effects, non-cardiogenic pulmonary oedema has become increasingly recognised as a rare, but possibly life-threatening complication. We present a case of a usually well, young 23-year-old female who developed non-cardiogenic pulmonary oedema with a moderate oxygenation impairment and no mucosal or cutaneous features of anaphylaxis following the administration of gadolinium-based contrast. She did not respond to treatment of anaphylaxis but made a rapid recovery following the commencement of positive pressure ventilation. Our case highlights the importance of recognising the rare complication of non-cardiogenic pulmonary oedema following gadolinium-based contrast administration in order to promptly implement the appropriate treatment.